SINTESIS SEMEN GEOPOLIMER BERBAHAN DASAR ABU VULKANIK DARI ERUPSI GUNUNG MERAPI - Bayuseno, Athanasius Priharyoto; Widyanto, Susilo Adi; Juwantono, Juwantono (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2010)
Recently, it has been paid more attention to reduce the carbon dioxide emision from cement industry by introducing the new technology of producing green cement. In the same time, the Merapi eruption has produced the million ton of volcanic ash which is potentially attractive for used as raw material of geopolimer. In this research, geopolymer material was sinthesized from volcanic ash and then mixed by alkaline solution of sodium hydroxide and sodium silicate at variation of heating temperature, heating time, and hardening time. The objective of this research was to study about feasibility of volcanic ash as raw material for making geopolymer materials and to determine the optimum process for getting high compressive strength as well as to determine the composition of geopolymer precursor. In this research, chemical composition of the volcanic ash was previously determined by XRF, while the phase composition of the geopolymer obtained by XRD analysis. Results show that volcanic ash contains alumina and silica as dominant compounds, while the mineral phase is dominated by Albite. The highest compressive strength of mortar is obtained at16,81 MPa, produced from specimens which were heated for 12 hours and at temperature of 80 OC, and aged for 30 days